If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
8/3-((6*x)/3) = 0
8/3-2*x = 0
8/3-2*x = 0 // - 8/3
-2*x = -8/3 // : -2
x = -8/3/(-2)
x = 4/3
x = 4/3
| 2m=15-m | | memfaktorkanbentukax2+bx+c denganatidaksamademgan1 | | 5x+20-9x=-10-50 | | x(2x-6)=(2x+2)(x-2) | | 7+6x=4x+7 | | 9t(4-6t)+17=37 | | 5x-20-9x=-3x-2x+10-50 | | 3y+9xy=20xfory | | 3y+9xy=20x | | 2(1.5c+4)=-1+0.75c | | 8x+4-2=x+6x+14 | | 3(a-b)/9_4/9b | | 7a*9a= | | */10 | | Az+4z=b | | 87-5x=40x+17 | | 140=56+7c | | 3x+6-(4x+12)=6+(2+1)x | | 6m^5n^3-24mn=0 | | 9+10x=39-31x | | 9x-10-5x+12=x+6-3x+10 | | 6p-1p=6 | | 3X=3.1 | | y=x+9byx | | Y+2.4y+1.7=1.7(y-3) | | 7y+3=3y+11 | | -14Y=1X-1 | | .2y=1.8y | | -3/8÷m=3/4 | | 13x+2=-11 | | 15X-2=10X-4 | | 8tan(6x)=3 |